ANALISIS DAYA SAING DAERAH DI JAWA TENGAH (Studi Kasus: Kota Semarang, Kota Salatiga, Kota Surakarta, Kota Magelang, Kota Pekalongan, dan Kota Tegal Tahun 2009-2011) - Anita Nur Milah; Hadi Sasana (Diponegoro Journal of Economics, 2014)
ABSTRACTArea of the city as a growth center or community center supposed to be more advanced in the region's economy, infrastructure, and also natural and human resources. In fact, the results of the level of competitiveness some of city regions in Central Java tends to be lower when compared to the district. This study aims to determine how the level of competitiveness of city regions in Central Java and the potential of what is contained by each of these areas.The study used the competitiveness analysis method, which calculates scores and the index during the period 2009-2011. Type of data used is secondary data obtained from the Central Statistics Agency (BPS) in Central Java, PLN Ltd. Company distribution Central Java, and other literature such as books, and economic journals.The results of the level of competitiveness of city regions in Central Java, among others Semarang get first rank at the level of competitiveness of city regions in Central Java from 2009 to 2011. While Tegal has lowest ranks in 2009 and 2011, and the lowest ranked is Magelang in 2010. Potential Semarang win on almost all indicators of competitiveness. The more winning potential of a region, the higher the level of competitiveness of the city region.